Sustainable healthy settlement on a small island as a cultural heritage area - I. Martias; R. Rifardi; A. Agrina; I. Suprayogi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Penyengat Island is a small island in the Riau Archipelago Province, Indonesia, with a coastal settlement that embodies traditional Malay values. This island holds significance due to the historical connection to the Malay royal civilization along the Malacca Strait, which includes Indonesia, Malaysia, and Singapore. Therefore, this research analyzes the status and determinants of the sustainability of healthy settlement arrangements in the coastal area of Penyengat Island as a cultural heritage site.METHODS: The study utilizes the multi-dimensional scaling-rapid appraisal for sustainability approach, employing the modified rapid appraisal for fisheries ordinance software technique for settlement analysis. Data collection was performed using a survey and literature review. The survey was conducted through field observations and interviews with respondents, while a literature review was carried out through secondary data collection related to settlements and cultural heritage. The data analysis was performed using multi-dimensional scaling, modified from the rapid assessment appraisal method for fisheries.FINDINGS: The study reveals that the sustainability index status for the ecological and institutional legal dimensions in Penyengat island is sustainable. In contrast, the economic and socio-cultural dimensions recorded low sustainability, while the green infrastructure dimension was deemed unsustainable. Several attributes significantly influenced the sustainability of healthy settlement arrangements in the coastal area of Penyengat Island, including household waste management, lighting in houses, noise levels, residential density, clean water supply, corporate social responsibility (CSR) funding, occupation, income growth, technological innovation, tourist numbers, public perception of the distance between cultural heritage and settlements, social conflicts, implementation of mutual cooperation, community group management, handling cross-program problems, education and training, settlement regulations, community organization regarding settlements, socialization of regulations, cultural heritage organizations, hedgerows, additional vegetation, tree canopy expansion, and rain gardens. The multi-dimensional scaling analysis indicated that the ecological dimension of sustainability ranged from 51.71 to 60.67, corresponding to the moderate status in Rukun Warga 1 to 5. The economic dimension ranges from 40.46 to 48.23, indicating a less advanced status in Rukun Warga 1 to 5. The socio-cultural dimension ranges from 48.97 to 51.78, representing sufficient status in Rukun Warga 1 and less sustainable in Rukun Warga 2 to 5. The institutional, legal dimension ranges from 50.18 to 71.24, with a sufficiently continuous status in Rukun Warga 1 to 5. Lastly, the green infrastructure dimension ranges from -0.12 to 6.72,  a non-continuous status in Rukun Warga 1 to 5.CONCLUSION: The sustainability status of healthy settlement arrangements on Penyengat Island is relatively good. While Penyengat Island has made significant strides in achieving sustainable settlement arrangements, the green infrastructure dimension requires attention. Enhancing sustainability in this dimension involves addressing socio-cultural aspects and improving the institutional and legal framework. In summary, Penyengat Island can progress toward a more sustainable and resilient future by fostering community involvement, strengthening governance structures, and implementing sustainable practices.